2013
DOI: 10.3109/08923973.2013.830124
|View full text |Cite
|
Sign up to set email alerts
|

β-mannosyl linkages inhibit CAWS arteritis by negatively regulating dectin-2-dependent signaling in spleen and dendritic cells

Abstract: The α-mannosyl linkages of Candida mannan is a key molecule for the immunotoxicity. CAWS727, which conatins β-mannosyl linkages, competitively bound to lectin receptors, and resulted in reductions in the inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“…4A to C). This result confirmed that sDectin-2-targeted liposome binding to the extracellular matrix was mannan specific, in agreement with the published carbohydrate specificity of sDectin-2 (4246). We examined the stability of binding of DEC2-AmB-LLs to C.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…4A to C). This result confirmed that sDectin-2-targeted liposome binding to the extracellular matrix was mannan specific, in agreement with the published carbohydrate specificity of sDectin-2 (4246). We examined the stability of binding of DEC2-AmB-LLs to C.…”
Section: Resultssupporting
confidence: 91%
“…Dectin-2 is encoded by the human and mouse C-type LECtin receptor gene CLEC6A. Dectin-2 binds α-mannans and N-linked and O-linked mannans in mannoproteins (4246). Dectin-2 is expressed in the plasma membrane of some lymphocytes, with its mannan binding domain (sDectin-2) on the outside of these cells and its signaling domain in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Unidentified RNA virus [25][26][27] Epstein-Barr virus 11,12) Candida albicans* 81) Human parvovirus B19 127) Human corona virus HCoV-NL63 121,122) Human vocavirus (HBoV) 125) Human immunodeficiency virus 124) Streptococcus pyrogenes 47) Staphyrococcus aureus 42,43) Yersinia pseudotuberculosis 76) Mycobacterium ssp 67) Lactobacillus casei* 130) α-mannan 87,132) β-glucan 128) Virus / Microbe dUTPase 15,123) TSST-1 35) SPEC 48) Possible effector molecule lipoarabinomannan 131) YPMa 64) Bacillus cereus 79) Candida ssp 72) A variant of Torque teno virus 7 126) Mycoplasma pneumoniae 129)…”
Section: Viruses Bacteria Fungiunclassified
“…KD-like vasculitis can be induced in rabbit, swine, and mouse models by various methods (80)(81)(82)(83). The known genetic background and ease of genetic manipulation have made mouse models the preferred model to investigate molecular pathogenesis of KD and to discover its therapeutic targets (84)(85)(86)(87)(88).…”
Section: Insight From Experimental Studies With Animal Model For Kdmentioning
confidence: 99%
“…This may explain why dectin-2 deficient mice are susceptible to C. albicans infection but, interestingly, not C. neoformans [148,149]. Dectin-2 may also detect -mannosyl linkages [150]. Dectin-2 can induce several cytokines and chemokines through multiple signalling pathways, including NF-B, MAPK, SYK, CARD9-Bcl10-Malt1, and PKC , and can activate the NLRP3 (NOD-like receptor family, pyrin domain containing 3) inflammasome and respiratory burst [87,151].…”
mentioning
confidence: 99%